Novel findings on ultrastructural protection of skeletal muscle fibers during hibernation of Daurian ground squirrels: Mitochondria, nuclei, cytoskeleton, glycogen. Issue 8 (11th January 2019) - Wang, Zhe; Jiang, Shan‐Feng; Cao, Jin; Liu, Kun; Xu, Shen‐Hui; Arfat, Yasir; Guo, Quan‐Ling; Chang, Hui; Goswami, Nandu; Hinghofer‐Szalkay, Helmut; Gao, Yun‐Fang
Abstract: We examined ultrastructure protective phenomena and mechanisms of slow and fast muscles in hibernating Daurian ground squirrels ( Spermophilus dauricus ). Some degenerative changes such as slightly decreased sarcomere length and vacuolization occurred in hibernation, but periaxonal capsular borders in intrafusal fibers remained distinct and the arrangement of extrafusal fibers and Z‐lines unscathed. In soleus samples, the number of glycogenosomes more than tripled during hibernation. The expression of phosphorylated glycogen synthase remained unaltered while that of glycogen phosphorylase decreased during hibernation. The number of extensor digitorum longus glycogenosomes decreased and the expression of phosphorylated glycogen synthase decreased, while glycogen phosphorylase expression remained unaltered. The nuclei number remained unchanged. Kinesin and desmin, preventors of nuclear loss and damage, were maintained or just slightly reduced in hibernation. The single‐fiber mitochondrial concentration and sub‐sarcolemmal mitochondrial number increased in both muscle types. The expression of vimentin, which anchors mitochondria and maintains Z‐line integrity, was increased during and after hibernation. Also, dynamin‐related protein 1, mitochondrial fission factor, and adenosine triphosphate synthase were elevated in both muscle types. These findings confirm a remarkable ultrastructure preservation and show an unexpected increase in mitochondrial capacity in hibernating squirrels. Abstract : We examined ultrastructure protective phenomena and mechanisms of slow and fast muscles in hibernating Daurian ground squirrels ( Spermophilus dauricus ). These findings confirm a remarkable ultrastructure preservation and show an unexpected increase in mitochondrial capacity in hibernating squirrels.